BUDAYA KOMUNIKASI ORGANISASI DEWAN PIMPINAN WILAYAH PARTAI KEBANGKITAN BANGSA SUMATERA UTARADALAM PEMILIHAN LEGISLATIF TINGKAT PROVINSI TAHUN 2014 - Alihot Sinaga (Al-Balagh : Jurnal Komunikasi Islam, 2017)
Abstrak: The Communication Culture Organization The Regional Executive Board of the North SumateraRebirth Party in the Provincial Legislative Election Year 2014, is a cultural study of organizational communicationin the Regional Leadership Council of the North Sumatera Awakening Party in 2014. Thisresearch uses research methods with empirical approach, the research specification is descriptive Analysis,which aims to provide an overview by qualitative methods of communication theories and the opinions ofexperts. From the research results can be explained that: the culture of organizational communication inthe Council of Regional Leaders of the North Sumatra National Awakening Party in the Provincial LegislativeElection Year 2014, in succeeding elections in 2014 The Regional Leadership Council of the NationalAwakening Party conducted a variety of winning strategies one of which is to keep building Andmaintaining the culture of communication that has been built in the people of North Sumatra, one of theculture of organizational communication in the Regional Leadership Council of the National AwakeningParty is the culture of communication through local wisdom, the culture of print and electronic mediacommunication, the culture of religious communication and the culture of kinship communication